The introspection on the diagnosis and treatment process of a case of Guillain–Barré syndrome (GBS) attributed to systemic lupus erythematosus (SLE): A case report. Issue 49 (December 2017) - Zhang, Nan; Cao, Jie; Zhao, Meng; Sun, Li
Abstract: Rationale: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory connective tissue disorder. It may cause neurologic damage which is mainly characterized by central and mental system, while peripheral sexual damage is relatively rare in which Guillain–Barré Syndrome (GBS) as the first performance is more rare . GBS is an autoimmune peripheral neuropathy usually triggered by an antecedent bacterial or viral infection, with SLE being a rare cause. Patient concerns: A 65-year-old male presented to the hospital with progressive numbness and adynamia in extremities. His vital signs were stable. 5 days later, his condition aggravated and mechanical ventilation was necessitated owing to severe dyspnea. Diagnoses: Based on the clinical symptoms and results of the lumbar puncture and electromyography, he was first diagnosed as GBS, however, after treatment his condition was deteriorate and the blood test showed abnormal immune indices, then renal biopsy was performed, which confirmed the diagnosis of peripheral nervous system in patients with systemic lupus erythematosus (PNS-SLE). Interventions: Firstly he was treated with intravenous immunoglobulin (IVIG) for 5 days. After his condition deterioration, he was conducted endotracheal intubation and, finally, a tracheostomy was performed. Later on he was treated with steroid therapy for several weeks. Outcomes: The patient showed remarkable recovery and was able to walk on his own by the time of discharge. Lessons: PNS-SLE can, by itself, be one of the main causes of morbidity and mortality. Electromyography and renal biopsy should be considered when relevant. Peripheral neuropathy in SLE should be given greater recognition, and rarer forms of presentation should be taken seriously in the differential diagnosis when the clinical picture is atypical. Glucocorticoids may play an important role in the treatment of PNS-SLE.